2001
DOI: 10.1006/mthe.2000.0238
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Stable Cell Line Producing High-Titer Self-Inactivating Lentiviral Vectors

Abstract: To facilitate the generation of SIN lentivirus vector-producer cell lines, we have developed a novel conditional SIN (cSIN) lentivirus vector, which retains its SIN properties in normal target cells yet can be produced at high titers from tetracycline-regulated packaging cell lines. The design of the cSIN vector is based on replacing the vector U3 transcription regulatory elements with the Tet-responsive element, which allows vector production exclusively in cells expressing the synthetic Tet-regulated transac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(121 citation statements)
references
References 17 publications
1
115
0
4
Order By: Relevance
“…Despite the simplicity and speed of this approach, relatively little progress has been made at large-scale. Only minor modifications of the protocol or optimization of the transient transfection parameters originally published by Naldini et al (1996b) have been reported (Coleman et al, 2003;Geraerts et al, 2005;Koldej et al, 2005;Mitta et al, 2005), which contrasts the many efforts devoted to the development of stable packaging cell lines (Farson et al, 2001;Kafri et al, 1999;Klages et al, 2000;Kumar et al, 2003;Ni et al, 2005;Pacchia et al, 2001;Xu et al, 2001). This may be due to the fact that transient transfection is still commonly regarded as a nonscaleable technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the simplicity and speed of this approach, relatively little progress has been made at large-scale. Only minor modifications of the protocol or optimization of the transient transfection parameters originally published by Naldini et al (1996b) have been reported (Coleman et al, 2003;Geraerts et al, 2005;Koldej et al, 2005;Mitta et al, 2005), which contrasts the many efforts devoted to the development of stable packaging cell lines (Farson et al, 2001;Kafri et al, 1999;Klages et al, 2000;Kumar et al, 2003;Ni et al, 2005;Pacchia et al, 2001;Xu et al, 2001). This may be due to the fact that transient transfection is still commonly regarded as a nonscaleable technology.…”
Section: Discussionmentioning
confidence: 99%
“…Production of lentiviral particles can be accomplished in two different ways: by development of stable vector packaging cell lines or by transient transfection of human cells. Although the generation of several stable packaging cell lines has been achieved (Farson et al, 2001;Kafri et al, 1999;Klages et al, 2000;Kumar et al, 2003;Ni et al, 2005;Pacchia et al, 2001;Xu et al, 2001), this method is hampered by the long time required to develop a stable cell line expressing all required vector components (typically >6 months) and the lack of compatibility with cytotoxic/cytostatic transgenes or vector components that entails the need for a tight control over gene(s) expression Sinn et al, 2005). Additionally, new packaging cell lines need to be developed for each desired vector pseudotype and for each generation of improved lentiviral vectors.…”
Section: Introductionmentioning
confidence: 99%
“…[11,22] Without any accessory genes, current lentiviral vectors are considered reasonably safe, because the replication of the vectors is highly inhibited and the possibility of recombination is reduced. [22,23] Recent work showed successful gene transfer by lentiviral vectors into quiescent T and B lymphocytes for immunotherapy of several genetic dysfunctions of the haematopoietic system. [24][25][26][27] Results from an ongoing lentivirus-based gene therapy trial in France for β-thalassaemia showed that one patient had not required blood transfusions for the past 16 months.…”
Section: Lentiviralmentioning
confidence: 99%
“…Stable packaging and producer cell lines have been developed for the production of human immunodeficiency virus 1-based LVs [14][15][16][17][18][19][20][21][22][23][24][25] but, to date, none have been described for EIAV-based LVs. The glycoprotein of the vesicular stomatitis virus (VSV-G) is often used for pseudotyping LVs because of its high stability, broad tropism and generation of high-titre viral stocks.…”
Section: Introductionmentioning
confidence: 99%
“…However, a complicating factor is that VSV-G is cytotoxic 26,29 and therefore its expression must be regulated. For many of the human immunodeficiency virus 1 based packaging cell lines VSV-G expression is controlled using tetracycline-inducible systems, 15,16,18,20,21,24 enabling VSV-G expression to be switched on at the time of vector production. In these systems, gene expression is controlled by expression of the tetracycline transactivator fusion protein comprising the tetracycline repressor (TetR) and the transcription activation domain of VP16.…”
Section: Introductionmentioning
confidence: 99%